Evaluasi Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) pada Proyek Persiapan Lahan Pusri IIB PT. Pupuk Sriwidjaja Palembang - Jula Nujhani; Ika Juliantina (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2013)
Safety and Health Management System (SMK3) should be noted. It is because of the high number of accidents. The purpose of SMK3 are to create a system of safety and health working in the workplace by involving elements of management, employees, conditions and environment thatÂ integrated in order to prevent and to decrease the accidents and occupational diseases and to create a safe, efficient and productive workplace. The applying of SMK3 at PT. Pupuk Sriwidjaja has been quite better since the applying guidance of SMK3 that is included in the report 1 PERMENAKER has been almost adapted by PT. Pupuk Sriwidjaja. The company had identified and recorded the risk that will be happened to all of the activities in the factory area. It also had communicated the rule and the guide of K3 to the contractors and partners by a meeting, electronic media and bulletin. By spreading a questionare that analyzed by the method of 'scoring' with the result toward the employees 77.75., team of contractor 88,5, team of supervisor 89, team of K3&LH 80.25. The applying of SMK3 to this project's preparation of pusri's field IIB included in the applying category of SMK3 which in fact, quite effective By presenting this evaluation, It's expected ,the company can keep the balance process of SMK3 that had been there so that we can be obtained a safety and healthy place for work so that theÂ productivity can beÂ improved.Keywords : accident, SMK3